2014
DOI: 10.1159/000356675
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Inhibits IL-1�-Induced CCL20 and IL-6 Production from Human Periodontal Ligament Cells

Abstract: Background/Aims: Genipin, the aglycon of geniposide found in gardenia fruit has long been considered for treatment of various diseases in traditional oriental medicine. Genipin has been used as a blue colorant in food industry. Genipin has recently been reported to have some pharmacological functions, such as antimicrobial, antitumor, and anti-inflammatory effects. The aim of this study was to examine whether genipin could modify CCL20 and IL-6, which are related to bone resorption in periodontal disease, expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Activation of NF-κB is essential for up-regulation of COX-2 caused by IL-1β in human gingival fibroblasts [21]. Suppression of NF-κB p65, ERK and MEK phosphorylations could down-regulate IL-1β-induced CCL20 and IL-6 production in human PDL cells [22]. In this study, we found a significant increase in expression of the NF-κB p65 subunit and NF-κB activity in PDL cells after nicotine stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB is essential for up-regulation of COX-2 caused by IL-1β in human gingival fibroblasts [21]. Suppression of NF-κB p65, ERK and MEK phosphorylations could down-regulate IL-1β-induced CCL20 and IL-6 production in human PDL cells [22]. In this study, we found a significant increase in expression of the NF-κB p65 subunit and NF-κB activity in PDL cells after nicotine stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor κB (NF‐κB) plays an important role in inflammatory responses, such as cytokine and chemokine production. We previously reported that IL‐1β activates the NF‐κB pathway in HPDLC (Shindo et al, ), and the NF‐κB pathway is positively associated with CCL20 and IL‐6 production. However, it is unclear whether the NF‐κB pathway is involved in CCL3 or CCL5 production in IL‐1β‐stimulated HPDLC (ISHC).…”
Section: Introductionmentioning
confidence: 92%
“…60 Genipin prevented IL-1β-mediated CCL20 and IL-6 production in HPDLCs through suppressing nuclear factor kappa B (NF-κB) p65, extracellular signal regulated kinase (ERK) and MAPK/ERK kinase (MEK) phosphorylations. 61 Both genipin and geniposide inhibited production of exudate and nitric oxide (NO). However, genipin possessed stronger anti-inflammatory activity than geniposide.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…118 Genipin was useful for treating periodontal disease by preventing MMPs expression like release of MMP-1, MMP-3 from TNF-α-stimulated human periodontal cells. 61 Crocetin revealed its hypnotic effect. 119 Even a single administration of Gardenia jasminoides extract exhibited rapid anti-depressant effects in reducing the number of escape failures in the learned helplessness test significantly and decreased latency of food consumption in the novelty suppressed-feeding test with the elevated expression of brain-derived neurotrophic factor (BDNF) expression in the hippocampus.…”
Section: Miscellaneous Activitiesmentioning
confidence: 99%